The Alliance between Mengu-Timur and Abaga: The Problem of Sources Interpretation and Translation of Persian and Turkic Terms in Arabic Texts (on the example of “Collection of Materials Relating to the Golden Horde History. Volume I. Excerpts from the Arabic Writings” composed by V.G. Tiesenhausen) » - Ihsan Fazlioğlu (Золотоордынское обозрение)
The Turkish author Ihsan Fazlioğlu presents to attention of readers the second part of the article “A Masterpiece of Computational Mathematics” (“et-Tuhfe fî ilmi’l-hisâb”). The author of this article presents the first example of an established scientific activity in the Golden Horde, which began before Janibek khan, during the reign of Uzbek khan. The work written in the Golden Horde on a mathematical topic occupies a special place because of the information contained therein. This treatise shows that the scientific activity in the Golden Horde, which began with the conversion to Islam, brought results in a short time and laid the foundations for “breakthroug” during the reign of Janibek khan. The author examines this composition from a historical perspective. The Computational book “et-Tuhfe fî ilmi’l-hisâb”, whose author is unknown, was handed during the reign of Uzbek Khan (1313–1342) to the ruler of the Crimean ulus of the Golden Horde Ebul-Muzaffer Giyaseddin Tuluktemir bey. After mentioning the distinguishing features of the work, the author pays particular attention to the definition of numbers, which is attributed to Muhammad b. Musa al-Khwarizmi and which, at the moment, is not recorded elsewhere. The author disputes the capacity for understanding of the evidence used in the calculation, surveying, and algebra, and will consider definitions with respect to the theory of numbers. Further, the author will analyze the formula of approximate values of square and cube roots of irrational numbers proposed by Muhammad al-Khwarizmi, Abdulkadir al-Baghdadi, and the teacher of the author, Saduruddin al-Farazi. This part examines the author of the work and features of his age as well as the scientific environment that contributed to the writing of the “et-Tuhfe fî ilmi’l-hisâb”. The article presents the contents of the work and familiarizes the reader with the scientists and their works, which are referenced by the author.